2000
DOI: 10.1046/j.1365-2370.2000.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of HLA‐A, ‐B, ‐DRB1, ‐DQA1 and ‐DQB1 haplotypes in a Croatian population

Abstract: We describe for the first time extended haplotypes in a Croatian population. The present study gives the HLA-A, -B, -DRB1, -DQA1 and -DQB1 allele and haplotype frequencies in 105 families with at least two offspring. All individuals were studied by conventional serology for HLA class I antigens (A and B), while class II alleles (DRB1, DQA1, DQB1) were typed using the PCR-SSOP method. HLA genotyping was performed by segregation in all 105 families. For extended haplotype analysis, 420 independent parental haplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 20 publications
6
31
2
Order By: Relevance
“…[19] Also, DRB11 rate was found 29% in Macedonians [20] and 15% in Croatians. [21] Temiz et al [14] reported that HLA Cw04 is the most and HLA cw 07 IS THE SECOND FREQUENT AL-LELE IN their population but we found that Cw07 is the most (28.7%) and Cw 04 is the second one (21.8%). Also, DQ allele results showed some dşffereneces with pur study.…”
Section: Discussioncontrasting
confidence: 72%
“…[19] Also, DRB11 rate was found 29% in Macedonians [20] and 15% in Croatians. [21] Temiz et al [14] reported that HLA Cw04 is the most and HLA cw 07 IS THE SECOND FREQUENT AL-LELE IN their population but we found that Cw07 is the most (28.7%) and Cw 04 is the second one (21.8%). Also, DQ allele results showed some dşffereneces with pur study.…”
Section: Discussioncontrasting
confidence: 72%
“…Alleles HLA-A*03 and HLA-B*0702 are in strong linkage disequilibrium (8,17). The original study by Moore et al (31) did not detect an association between HLA-A*0301 and E169D independent of HLA-B*0702.…”
Section: Resultsmentioning
confidence: 97%
“…Position 169 also maps within an overlapping HLA-A*0301-restricted epitope, MR9 (aa 164 to 172). Despite the strong linkage disequilibrium between HLA-A*0301 and B*0702 and the high frequency of HLA A*03 in the population (8,17), statistical association between E169D and HLA-A*0301, independent of HLA-B*0702, has not been found.…”
Section: Ei69d Mutation Abolishes the Ctl Recognition Of The Neighbormentioning
confidence: 91%
“…In total, 94 individuals (average age 32, range 22-59) were screened to obtain HLA-A*0201 + group of adult healthy volunteers. HLA-A*02 + status was tested using the microlymphocytotoxicity (MLCT) serological technique [13] and ⁄ or fluorescein isothiocyanate anti-HLA-A*02 antibody (Proimmune, Oxford, UK). HLA-A*0201 typing was performed using polymerase chain reaction with sequence-specific primers (PCR-SSP) as described previously [14].…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%